Reconstruction error of calibration volume's coordinates for 3d swimming kinematics - Figueiredo, P.; Vilas-Boas, J. P.; Fernandes, R. J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to investigate the accuracy and reliability of above and underwater 3D reconstruction of a calibration volume used for swimming analysis. The calibration volume (3x2x3m3) was positioned half above and half below the water surface. Recordings with four underwater and two above water synchronised cameras were done and DLT algorithm used to estimate marker locations. Reconstruction accuracy was determined by the RMS error of 12 validation points and reliability by the standard deviation of all digitisations of the same marker. Comparison among different number of control points showed the set of 24 points to be the most accurate for both environments. Although, the RMS values above water were lower than the RMS values presented underwater. The calibration volume was found to have high accuracy and reliability.